오정정 없이 온칩 메모리 보호를 위한 SEC-DED-DAEC 부호 - 전호윤(Hoyoon Jun) (한국정보통신학회논문지, 2022)
As electronic devices technology scales down into the deep-submicron to achieve high-density, low power and high performance integrated circuits, multiple bit upsets by soft errors have become a major threat to on-chip memory systems. To address the soft error problem, single error correction, double error detection and double adjacent error correction (SEC-DED-DAEC) codes have been recently proposed. But these codes do not troubleshoot mis-correction problem. We propose the SEC-DED_DAEC code with without mis-correction. The decoder for proposed code is implemented as hardware and verified. The results show that there is no mis-correction in the proposed codes and the decoder can be employed on-chip memory system.